The Summa Halensis. Sources and Context - Schumacher, Lydia (Veröffentlichungen des Grabmann-Institutes zur Erforschung der mittelalterlichen Theologie und Philosophie, 2020)
For generations, early Franciscan thought has been widely regarded as unoriginal: a mere attempt to systematize the longstanding intellectual tradition of Augustine in the face of the rising popularity of Aristotle. This volume brings together leading scholars in the field to undertake a major study of the sources and context of the so-called Summa Halensis (1236-45), which was collaboratively authored by the founding members of the Franciscan school at Paris, above all, Alexander of Hales, and John of La Rochelle, in an effort to lay down the Franciscan intellectual tradition or the first time. The contributions will highlight that this tradition, far from unoriginal, laid the groundwork for later Franciscan thought, which is often regarded as formative for modern thought. Furthermore, the volume shows the role this Summa played in the development of the burgeoning field of systematic theology, which has its origins in the young university of Paris. This is a crucial and groundbreaking study for those with interests in the history of western thought and theology specifically.